(untitled) (Bangladesh Journal of Nutrition, 2013)
A cross sectional study was carried out to investigate the effects of socio-economic, demographic and internet exposure factors on school performance among 10 grade students of Nilkhet High School. All of the eighty seven students were selected for this study. In this study school performance was measured by class roll number. The lower the class roll number the better the school performance. During Chi-square test grade (A+, A, A-, B, C, D) achieved in the class 9 final examination was taken as dependent variable. An upper grade indicates better school performance than lower grade. Class roll number were highly negatively correlated with the factors-actual income of the family, actual monthly tuition cost, number of rooms in the house, number of earning persons in the family, and this correlation was significant (p<0.01) at 1% level of significance. Chi-square test was used to check for association between the category of these factors and the school performance measured by grade. Chi-square test also found highly significant. In Chi-square test some of the other factors namely highest education of mothers (p<0.05), highest education of fathers (p<0.05), occupation of fathers (p<0.01), and occupation of mothers (p<0.05) were significant. Maximum 80.7% change in school performance was found when we studied the aggregate effects of fourteen factors. The school performance measured by grade of the students was significantly related with the work on internet and number of friends in Facebook because the Chi-square test shows the P-value<0.01. Maximum 43.5 % changes occurred in school performance when number of friends in Facebook was significant at 1% level of significance and both work on internet and Facebook account were significant at 10% level of significance. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14041 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.107-120